Assessment of respiratory symptoms and peak expiratory flow rate among brick kiln workers in Bhaktapur - Khakurel, Gita; Gautam, Kalyan; Kumar Karki, Prabin (Journal of Chitwan Medical College, 2025)
Introduction: Brick kiln workers are exposed to high concentrations of dust and smoke, predisposing them to respiratory problems and impaired lung function. The objective of this study was to assess the prevalence of respiratory symptoms and evaluate peak expiratory flow rate among these workers in Bhaktapur. Method: A cross-sectional study was conducted among brick kiln workers from three brick kilns in Bhaktapur district between 02 Apr to 30 Jun 2025 after obtaining ethical approval. Sample size was calculated to be 267. Using a 2:1 ratio of workers:unexposed controls, 178:89, aged ≥18 years, were matched for age and compared for respiratory symptoms and peak expiratory flow rate. Student t-test was used to assess the difference in the mean of peak expiratory flow rate, with p<0.05 considered statistically significant. Result: The prevalence of respiratory symptoms among 178 brick kiln workers was 32(17.97%) for chronic cough, 23(12.9%) for phlegm, 19(10.7%) for shortness of breath, 20(11.2%) for chest pain, and 10(5.6%) for wheezing. The mean peak expiratory flow rate of brick kiln workers, 415.17±53.09 L/min was significantly lower than that of the control group, 499.25±19.89 L/min (p<0.001). Within the brick kiln workers, smokers had a significantly reduced mean peak expiratory flow rate of 376.86±22.59 L/min compared to non-smokers 475.70±21.37 L/min (p< 0.001). Conclusion: Brick kiln workers in Bhaktapur have a high prevalence of respiratory symptoms and significantly reduced peak expiratory flow rate, particularly among smokers.